2013
DOI: 10.1007/s00540-013-1731-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative morphological analysis by transesophageal echocardiography and predictive value of plasma landiolol concentration during systolic anterior motion mitral valve repair : a report of three cases

Abstract: We report three cases with systolic anterior motion (SAM) after mitral valve plasty. Preoperative mitral valve morphology is a risk factor for SAM. The morphological characteristics of SAM have been revealed in several studies. We found a small distance between coaptation and the interventricular septum in all cases, and cases 2, and 3 had a low AL/PL ratio, whereas case 3 had a large PML, which was revealed by transesophageal echocardiography. With the use of 3D transesophageal echocardiography, when mitral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The first important result of our study can be found in the basic geometry of the Coaptation Triangle and its two most important measurements, antero‐posterior diameter and coaptation depth, which resulted 31.4 mm and 7.4 mm, respectively. These values agree with literature findings, which report normal dimensions ranging from 26 to 32 mm for the antero‐posterior diameter and 5–9 mm for the coaptation depth . An interesting aspect of these dimensions is that they seem dependent on the geometry of the GCT.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The first important result of our study can be found in the basic geometry of the Coaptation Triangle and its two most important measurements, antero‐posterior diameter and coaptation depth, which resulted 31.4 mm and 7.4 mm, respectively. These values agree with literature findings, which report normal dimensions ranging from 26 to 32 mm for the antero‐posterior diameter and 5–9 mm for the coaptation depth . An interesting aspect of these dimensions is that they seem dependent on the geometry of the GCT.…”
Section: Discussionsupporting
confidence: 91%
“…The PC/AC ratio we obtained was 0.60, a number which is very close to the value of ϕ. Recent investigations on valve performance after conservative surgery concluded that an AC/PC ratio lower than 1.5 indicates a too anterior displacement of the coaptation point and significantly increases the risk for systolic anterior movement after mitral repair . Like the coaptation depth, the correct position of the coaptation point could be calculated geometrically.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations